PENGARUH TINGKAT HUNIAN HOTEL, JUMLAH OBJEK WISATA, DAN PAJAK HOTEL TERHADAP PENDAPATAN ASLI DAERAH KABUPATEN BERAU - Ira Indriani (ECO-BUILD, 2025)
The purpose of this study was to determine and analyze the effect of hotel occupancy rates, number of tourist attractions, and hotel taxes on the Regional Original Income of Berau Regency. Secondary data in the form of hotel occupancy rates, number of tourist attractions, regional taxes, and regional original income in Berau Regency during 2017-2022. The analysis tools used are: Classical assumption test, multiple linear regression, correlation coefficient, determination coefficient, t-test, and F-test. This study concludes that: 1) Hotel occupancy rates have a significant partial effect on PAD of Berau Regency in the period 2017-2022. Based on the results of the t-test, where the t-count value is greater than the t-table value (4.716> 4.303) and the significance value is smaller than the probability value (0.042 <0.05); 2) The number of tourist attractions has a significant partial effect on PAD of Berau Regency in the period 2017-2022. Based on the results of the t-test, where the t-count value is greater than the t-table value (4.355> 4.303) and the significance value is smaller than the probability value (0.049 <0.05); 3) Hotel tax does not have a significant partial effect on PAD of Berau Regency in the period 2017-2022. Based on the results of the t-test, where the t-count value is smaller than the t-table value (0.835 <4.303) and the significance value is greater than the probability value (0.492> 0.05); and 4) Hotel occupancy rate, number of tourist attractions, and hotel tax have a significant effect simultaneously on PAD Berau Regency in the period 2017-2022. Based on the results of the F-test, where the F-count value is greater than the F-table value (49.319> 19.16) and the significance value is smaller than the probability value (0.020 <0.05).